2012
DOI: 10.1136/jech-2011-200307
|View full text |Cite
|
Sign up to set email alerts
|

Does social capital affect the incidence of functional disability in older Japanese? A prospective population-based cohort study

Abstract: Lower community social capital was associated with higher incidence of onset of functional disability among older women but not among men. Community-based interventions to promote social capital may be useful for preventing functional disability of older Japanese women.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

8
85
2
8

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 83 publications
(103 citation statements)
references
References 35 publications
8
85
2
8
Order By: Relevance
“…Our results corroborate findings of international studies carried out in the higher income countries 15,26,27 . In addition to that, our results showed that not all elements of the social capital are associated to the functional disability, as its association was restricted to the indicator of cohesion to the household.…”
Section: Discussionsupporting
confidence: 82%
See 3 more Smart Citations
“…Our results corroborate findings of international studies carried out in the higher income countries 15,26,27 . In addition to that, our results showed that not all elements of the social capital are associated to the functional disability, as its association was restricted to the indicator of cohesion to the household.…”
Section: Discussionsupporting
confidence: 82%
“…The identification of associated factors that causes functional disability of elderly provides relevant elements for the prevention and for the intervention strategies and it is essential to avoid or lessen the damages to the individuals, the family, and the society. From what is known, few studies have been examining social factors as the determinants of functional disability 15,27 . In addition to that, considering the social capital proves particularly important, as it provides opportunities for better understanding the reason why inequalities in health are manifested, especially the functional disability, and how they may be better addressed, directing the focus of health professionals, policies, and the community members themselves, in favor of aging with quality of health 31 .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Social environments encompass multiple dimensions that may influence people's health status (Aida et al, 2013;Fujiwara et al, 2008;Kawachi et al, 1997b;Kobayashi et al, 2013;Zarzar et al, 2012) and mortality risk (Cubbin et al, 2000;Waitzman et al, 1998). One important dimension of the social environment is social capital.…”
Section: Introductionmentioning
confidence: 99%